Historiographia linguistica. International Journal for the History of Linguistics. Revue internationale pour l’histoire de la linguistique. Internationale Zeitschrift für die Geschichte der Sprachwissenschaft. T. 1, núm. 1, 1974, 145 pp. John Benjamins, Amsterdam, Holland. - Garza Cuarón, Beatriz (Nueva Revista de Filología Hispánica (NRFH), 1974)
Se reseñó: Historiographia linguistica. International Journal for the History of Linguistics. Revue internationale pour l'histoire de la linguistique. Internationale Zeitschrift für die Geschichte der Sprachwissenschaft.